COMPARISON OF SEED PROTEINS ELECTROPHORESIS OF EIGHT SPECIES OF THE GENUS SUAEDA (CHENOPODIACEAE) IN IRAN (Journal of Sciences, Islamic Republic of Iran)
Seed proteins of eight species of the genus Suaeda (Chenopodiaceae) were compared by means of polyacrylamide disc gel electrophoresis. Different samples of the same species showed not less than 89% similarities, and geographical separation had no remarkable effect on seed protein patterns of the same species. Morphological heterogenity, that creates difficulties in infrageneric classification, was also evident in clustering analysis of protein bands. S. microsperma, which is morphologically very close to S. acuminata, was found a great distance away from any other species